BUILDING EMPLOYEE PERFORMANCE THROUGH WORKPLACE SPIRITUALITY: A BIBLIOMETRIC AND SYSTEMATIC LITERATURE REVIEW - Emi Puspita Dewi; Isnurhadi; Zunaidah; Muhammad Ichsan Hadjri (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
Employee performance is a critical factor influencing organizational effectiveness, competitiveness, and long-term sustainability. In recent years, workplace spirituality has gained increasing scholarly attention as an organizational resource that promotes meaningful work, interpersonal connectedness, ethical values, and employee wellbeing. This study aims to examine the intellectual structure, research trends, and thematic development of workplace spirituality in relation to employee performance through an integrated bibliometric analysis and systematic literature review. Bibliometric data were retrieved from the Scopus database using relevant keywords related to workplace spirituality and employee performance, while the review process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) guidelines to ensure a transparent and systematic selection of studies. Bibliometric mapping was conducted using VOSviewer to visualize keyword co-occurrence, research clusters, and conceptual relationships among the identified themes. The systematic review synthesized empirical findings from the selected studies to identify the mechanisms through which workplace spirituality contributes to employee performance. The findings reveal that workplace spirituality is closely associated with employee engagement, work engagement, job satisfaction, organizational commitment, organizational citizenship behavior, and psychological wellbeing, all of which contribute to improved employee performance. The bibliometric network further indicates that religiosity, spirituality, ethical leadership, and organizational culture constitute important supporting themes within the development of this research field. Despite the growing body of literature, limited studies have integrated workplace spirituality with contemporary organizational capabilities and sustainable human resource management perspectives. This study contributes by providing a comprehensive overview of the intellectual landscape of workplace spirituality research and proposing future research directions to strengthen organizational strategies for improving employee performance through meaningful work environments and positive organizational values.